2016
DOI: 10.1002/ppap.201500211
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Plasma Polymer of Ethyl Lactate: In Vitro Degradation and Cell Viability Studies

Abstract: Ethyl lactate is injected into a dielectric barrier discharge (DBD) to build up a degradable plasma polymer (PP) to be used as a drug delivery system. Plasma power, deposition time, and type of carrier gas (Ar, N 2 ) are correlated to the coating in vitro degradation rate. PPs are characterized by AFM, SEM, IR spectroscopy, XPS, and SEC, while surface profilometry is used to monitor the degradation kinetics. PPs deposited under N 2 are mainly composed of hydrophilic functionalities, which explain their fast de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…We evaluated the areas under two sets of bands, (a) the normalized CH 2 /CH 3 stretch band just discussed ( A (CHx) ), and (b) the normalized CO stretch band near 1753 cm −1 ( A (C=O) ), then calculated the area ratios A (C=O) / A (CHx) , and show in Figure (b) a plot of these versus the corresponding E m values: E m = 0 represents spectrum A, the pristine liquid monomer, while data points to the right of it, respectively, represent spectra E, D, and C. The reason for selecting the CO absorption band for this purpose is that its intensity represents a reliable diagnostic for the extent to which structure of the EL monomer molecule [see (1)] is retained in the PP‐EL deposit. One notes from Figure (b) that the four data points (A, E, D, C) very closely follow a straight line plot; calculation of the regression line enabled extrapolation of the data point for spectrum B, the one representing the PP‐EL deposit (designated “EL‐Ar PP 2”) of Laurent et al On the basis of this argumentation, we can surmise that their corresponding E m value was close to 59 eV/molecule.…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…We evaluated the areas under two sets of bands, (a) the normalized CH 2 /CH 3 stretch band just discussed ( A (CHx) ), and (b) the normalized CO stretch band near 1753 cm −1 ( A (C=O) ), then calculated the area ratios A (C=O) / A (CHx) , and show in Figure (b) a plot of these versus the corresponding E m values: E m = 0 represents spectrum A, the pristine liquid monomer, while data points to the right of it, respectively, represent spectra E, D, and C. The reason for selecting the CO absorption band for this purpose is that its intensity represents a reliable diagnostic for the extent to which structure of the EL monomer molecule [see (1)] is retained in the PP‐EL deposit. One notes from Figure (b) that the four data points (A, E, D, C) very closely follow a straight line plot; calculation of the regression line enabled extrapolation of the data point for spectrum B, the one representing the PP‐EL deposit (designated “EL‐Ar PP 2”) of Laurent et al On the basis of this argumentation, we can surmise that their corresponding E m value was close to 59 eV/molecule.…”
Section: Resultsmentioning
confidence: 65%
“…In this research we have, once again, shown that the methodology portrayed in Figure allows one to perform DBD‐based AP PECVD experiments of unprecedented precision and reproducibility, used here to create PP‐EL deposits with ethyl lactate monomer [EL, see (1)]. PP‐EL deposits are thought to be excellent candidates for bio‐medical applications on account of the non‐toxic nature demonstrated by several authors . We have shown that a narrow range of E m values in Figure , between roughly 21 and 42 eV/molecule, lead to PP‐EL coatings of widely varying structural and physical properties, including ones with controlled retention of chemical features of the monomer, and a predictable rate of degradation in aqueous media.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations